Variables influencing delay in antenatal clinic attendance among teenagers in Lesotho - Semakaleng H. Phafoli; Elsie J. van Aswegen; Ursula U. Alberts (South African Family Practice)
Background: A delay in deciding to seek antenatal care is predominant among pregnant teenagers in Lesotho. This subsequently leads to delay in reaching treatment and in receiving adequate treatment. Early antenatal care attendance plays a major role in detecting and treating complications of pregnancy and forms a good basis for appropriate management during delivery and after childbirth. Although antenatal care is provided at different levels, Lesotho still has a high maternal mortality rate, estimated at 762 per 100 000 live births, and an infant mortality rate of 72 per 1 000 live births.1 Lesotho has a chronic shortage of doctors and nurses. According to the Lesotho Population Data Sheet of 2000, the doctor-patient ratio for this country for the year 1999 was 1:13 041 and the nurse ratio was 1:2 035. About 31% of the adult population between the ages of 15 to 49 years is infected with HIV/Aids.1 This shortage of health care personnel and the impact of HIV/Aids result in insufficient focus on health promotion in reproductive health, especially birth preparedness, and lack of community participation and male involvement in reproductive health care issues. Early sexual activities with consequent early pregnancy lead to high maternal and neonatal morbidity and mortality. As a result, the National Adolescent and Development Programme was started in 1998 by the Ministry of Health and Social Welfare to address the needs of teenagers. This led to the establishment of adolescent health clinics (referred to as teenage corners) that focus on teenagers in three districts of Lesotho, namely Mafeteng, Maseru and Leribe.Despite the establishment of these teenage corners, delay in antenatal attendance is still prevalent in Lesotho. Out of 632 pregnant teenagers in 2003 who attended the clinic at Queen II Teenage Corner, the majority (43%) visited the antenatal clinic for the first time during the third trimester and only 14.9% attended in the first trimester. This late antenatal clinic attendance provides little or no time for appropriate screening, management of risk factors, if detected, and timely referral. The aim of this study was to identify variables that contribute to delay in antenatal clinic attendance among pregnant teenagers and to make recommendations based on the research findings for the development of policies that will ensure early attendance.